Konwergencja fiskalna a członkostwo w Unii Europejskiej oraz w Unii Gospodarczej i Walutowej - Breza, Marzena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article is about monetary integration in the European Union. The author concentrates on the fiscal convergence process in the candidate countries to EMU. The problem of divergence between euro zone and new EU members is still present especially when we are taking into account economic situation in Poland. This article contains also an analysis of convergence between founders countries and an economic situation of the countries which candidate to Euro zone. The research indicates the fact that full economic convergence is a very difficult process. It is mainly because of the lack of the public finance stability. The author considers different national programme of stabilization (present every year in the Convergence Report), which are realized to achieve permanent fiscal balance. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 190-199